Influence of neurovascular anatomy on perforation site in different mouse strains using the filament perforation model for induction of subarachnoid hemorrhage - Weyer, Vanessa; Maros, Máté E.; Kirschner, Stefanie; Krost-Reuhl, Samantha; Groden, Christoph; Kramer, Martin; Brockmann, Marc A.; Kronfeld, Andrea (PLOS ONE, 2022)
Background Filament perforation is a widely-used method to induce subarachnoid hemorrhage (SAH) in mice. Whereas the perforation site has been assumed to be in the branching of middle cerebral artery (MCA) and anterior cerebral artery (ACA), we recently observed more proximal perforations. Methods Filament perforation was performed in CD1- (n = 10) and C57Bl/6N-mice (n = 9) ex vivo. The filament was left in place and the perforation site was microscopically assessed. Digital subtraction angiography (DSA) was performed in CD1- (n = 9) and C57Bl/6J-mice (n = 29) and anatomical differences of the internal carotid artery (ICA) were determined. Results Whereas in C57Bl/6N-mice perforation occurred in the proximal intracranial ICA in 89% (n = 8), in CD1-mice the perforation site was in the proximal ICA in 50% (n = 5), in the branching between MCA and ACA in 40% (n = 4), and in the proximal ACA in 10% (n = 1). DSA revealed a stronger angulation (p<0.001) of the ICA in CD1-mice (163.5±2.81°) compared to C57Bl/6J-mice (124.5±5.49°). Body weight and ICA-angle showed no significant correlation in C57Bl/6J- (r = -0.06, pweight/angle = 0.757) and CD1-mice (r = -0.468, pweight/angle = 0.242). Conclusion Filament perforation in mice occurs not only at the hitherto presumed branching between MCA and ACA, but seems to depend on mouse strain and anatomy as the proximal intracranial ICA may also be perforated frequently.